Complaint Handling: The Technique that (Almost) Nobody In the Conflict Resolution World Talks About. Issue 7 (30th June 2020) - Samuel, Adam
Abstract : In the dispute resolution world, there is a tendency to see a dispute and then a variety of techniques that one can use to resolve it: mediation, negotiation, arbitration, litigation and numerous other options.